2016
DOI: 10.1093/brain/aww138
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine restores the response inhibition network in Parkinson’s disease

Abstract: Impairments in response inhibition in Parkinson’s disease may reflect loss of noradrenaline and impaired fronto-subcortical connectivity. Rae et al. show that the noradrenaline reuptake inhibitor atomoxetine can restore functional connectivity in the inhibition network. Individual treatment responses depend on disease severity, plasma drug concentration and anatomical connectivity within the network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 88 publications
5
98
1
Order By: Relevance
“…Dysfunction of the latter circuit in FTLD can cause the failure to self-generate motor patterns, over and above blunted affect or cognitive dysfunction, in keeping with evidence for this circuit in voluntary action selection in health [20,28] and poor signal-to-noise in motor plans arising from the medial frontal cortex [29]. This ‘auto-activation’ deficit can also be formulated as a failure to reach a necessary activation threshold, by leakage, decay or refractoriness in the fronto-parietal neuronal ensembles that represent actions [17].…”
Section: Introductionmentioning
confidence: 70%
“…Dysfunction of the latter circuit in FTLD can cause the failure to self-generate motor patterns, over and above blunted affect or cognitive dysfunction, in keeping with evidence for this circuit in voluntary action selection in health [20,28] and poor signal-to-noise in motor plans arising from the medial frontal cortex [29]. This ‘auto-activation’ deficit can also be formulated as a failure to reach a necessary activation threshold, by leakage, decay or refractoriness in the fronto-parietal neuronal ensembles that represent actions [17].…”
Section: Introductionmentioning
confidence: 70%
“…; Rae et al . ). Direct projections from the LC to the STN might support interactions between the NA, the motor and the executive systems (Parent and Hazrati ).…”
Section: Discussionmentioning
confidence: 97%
“…; Chamberlain and Robbins ; Mather and Harley ; Rae et al . ; Borodovitsyna et al . ; Nahimi et al .…”
mentioning
confidence: 99%
“…Task-free resting state functional connectivity analysis showed that atomoxetine enhanced connectivity between the RIFG and the dorsal anterior cingulate in Parkinson's disease, hence generally boosting the fronto-striatal circuitry associated with SSRT performance (Borchert et al 2016). More specifically, the fMRI results with Parkinson's disease patients suggest that atomoxetine increases sensitivity of the inferior frontal gyrus to afferent inputs from the pre-supplementary motor cortex; and further that atomoxetine enhances downstream modulation of frontal-subcortical connections for response inhibition (Rae et al 2016). These effects may correspond to the effects of intra-PFC atomoxetine in rats described above and provide a possible explanation of some of the therapeutic effects of the drug in ADHD, as well as Parkinson's disease.…”
Section: Translation From Laboratory To Clinic Of Findings On Impulsimentioning
confidence: 97%